Metal-oxide interaction for metal clusters on a metal-supported thin alumina film - Libuda, Jörg; et al. (Surface Science, 1999)
The interaction between deposited metal clusters and a thin model alumina film grown on NiAl(110) have been studied using X-ray absorption spectroscopy (XAS) and core and valence photoelectron spectroscopy. A lower limit for the fundamental gap of the supported alumina film is determined, and found to be slightly lower than that of alumina surfaces. O 1s XAS shows that new states appear in the fundamental gap upon metal deposition. Al 2p X-ray photoelectron spectra from the alumina film are also sensitive to metal deposition, whereas spectra from Al atoms at the substrate-oxide interface appear unaffected. The present data demonstrate the existence of gap states in the pristine film, and we discuss the effects of these states for the properties of this film as a model oxide substrate. (C) 1999 Elsevier Science B.V. All rights reserved.
Keywords: alumina; metal clusters; metal-oxide; thin film; X-ray absorption spectroscopy